Literacy in History among Form Six Students - Jabar, Baharuddin; Saadon, Ramli; Sauman@Sabin, Yunus; Kamal Kamaruddin, Mohamad (International Journal of Psychosocial Rehabilitation, 2019)
This study aims at investigating the literacy level in history among Form Six students in Selangor, one of the states in Malaysia. Three domains of literacy in history are investigated in this study: knowledge, skills, and values. A set of questionnaires consisting of multiple-choice items related to history has been used as the research instrument and was developed by the researchers. The research participants selected are 347 Form Six students in Selangor. The data collected is analysed descriptively to identify the participants’ level of literacy in history. The findings have indicated the level of literacy in history for all three domains: domain of knowledge is 70.30%, domain of skills is 64.64%, and domain of values is 79.23%. The overall literacy in history is 71.39%